Expression of nerve growth factor receptors by Schwann cells of axotomized peripheral nerves: ultrastructural location, suppression by axonal contact, and binding properties - Taniuchi, M (J Neurosci, 1988)
Axotomy of sciatic nerve fibers in adult rats induces expression of NGF receptor in the entire population of Schwann cells located distal to the injury (Taniuchi et al., 1986b). In the present study we have used immunocytochemistry, with a monoclonal antibody directed against the rat NGF receptor, to examine axotomized peripheral nerves by light and electron microscopy. We have found that (1) the NGF receptor molecules were localized to the cell surface of Schwann cells forming bands of Bungner; (2) axonal regeneration into the distal portion of sciatic nerve coincided temporally and spatially with a decrease in Schwann cell expression of NGF receptor; (3) Schwann cell NGF receptor could be induced by axotomy of NGF-independent neurons, such as motoneurons and parasympathetic neurons; and (4) the presence of axon-Schwann cell contact was inversely related to expression of Schwann cell NGF receptor. Using biochemical assays we have found that, in striking contrast to peripheral nerves, there was no detectable induction of NGF receptor in the spinal cord and brain after axotomy of NGF receptor- bearing fibers. Filtration assays of 125I-NGF binding to the induced NGF receptors of Schwann cells measured a Kd of 1.5 nM and a fast dissociation rate, both characteristics of class II receptor sites. We conclude that Wallerian degeneration induces Schwann cells, but not central neuroglia, to produce and position upon their plasmalemmal surface the class II NGF receptor molecules. The induction is ubiquitous among Schwann cells, irrespective of the type of axon they originally ensheathed. Expression of Schwann cell NGF receptor is negatively regulated by axonal contact, being induced when axons degenerate and suppressed when regenerating axons grow out along the Schwann cell surface. We propose that the induced NGF receptors function to bind NGF molecules upon the Schwann cell surface and thereby provide a substratum laden with trophic support and chemotactic guidance for regenerating sensory and sympathetic neurons.